Analisis Kerusakan Jalan dan Biaya Pemeliharaan pada Ruas Jalan Raya Stain, STA 0+000 – 3+050: Analysis of Road Damage and Maintenance Costs on the Stain Highway Section, STA 0+000 - 3+050 - Gunawan, Gunawan; Metekohy, Selly; Marantika, Meyke (Litera Academica Publishing, 2025)
The road is a land transportation infrastructure that is very important in facilitating economic relations activities, both between one city and another, and between cities and villages and between one village and another. Good flexible pavement, must have quality and thickness which will not be damaged due to vehicle loads. Howefer, infrastructure that is burdened by high volumes of traffic and repeatedly will cause a decline in road quality. This study aims to assess the road pavement conditions and the level of road alignment on road sections to determine the type and level of road damage that occurs on the road, find and determine handling or maintenance based on damage. Calculating the value of road damage, to determine the condition of road damage and the level of road flatness is to use the pavement condition index (PCI) and presen serviceability index (PSI) methods. after going through several stages of data collection and data analysis using the pavement condition index (PCI) method and the present serviceability index (PSI), It can be concluded that the condition of the stained highway section with a length of 3050 m has 3 types of damage occurring. The results obtained from data analysis on damage to stained highway sections, obtained a PCI value of 68 with a moderate rating (fair) based on the pavement condition index (PCI) rating, while for the present serviceability index (PSI) the PSI value was 2 categorized as sufficient. In the budget plan for overlay work with a road length of 3050 m, the total work costs are obtained 9.276.317.158 (Four billion six hundred eighty seven million nine hundred and fifty thousand rupiah).